2002
DOI: 10.1108/13565360210445023
|View full text |Cite
|
Sign up to set email alerts
|

Effect of gamma radiation onto the properties of TeO2thin films

Abstract: The effects of γ‐radiation on both the optical and the electrical properties of Tellurium dioxide (TeO2) thin films were investigated. TeO2 thin films were fabricated using thermal vacuum deposition method. Samples were exposed to a 60Co γ‐radiation source with a dose rate of 6 Gy/min. Absorption spectra for TeO2 thin films were recorded and values of the optical band gap for as‐deposited and γ‐irradiated films were calculated. Sets of measurements based on Hall effect were carried out. From the data received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…These findings are in line with the results reported earlier for TeO 2 thin films, since the optical properties of thermally deposited TeO 2 thin films having a thickness of 50 nm also have shown a high sensitivity to gamma radiation [9,10]. Typical plots of the absorption spectra for as-deposited and γ-irradiated thin films (a) (b) of TeO 2 are shown in Fig.…”
Section: Resultssupporting
confidence: 91%
“…These findings are in line with the results reported earlier for TeO 2 thin films, since the optical properties of thermally deposited TeO 2 thin films having a thickness of 50 nm also have shown a high sensitivity to gamma radiation [9,10]. Typical plots of the absorption spectra for as-deposited and γ-irradiated thin films (a) (b) of TeO 2 are shown in Fig.…”
Section: Resultssupporting
confidence: 91%
“…The data revealed that the sheet resistance linearly decreased from 36.4 to 28.7 with an increase in radiation dose up to a level of 108 Gy [16]. The mobility and Hall coefficient increased for these films.…”
Section: A Dosimeters Based On Metal Oxide Filmsmentioning
confidence: 87%
“…The values of sheet resistance for as-deposited and gamma irradiated thin film samples having a thickness of 220 nm were measured with a four-point probe [16]. The data revealed that the sheet resistance linearly decreased from 36.4 to 28.7 with an increase in radiation dose up to a level of 108 Gy [16].…”
Section: A Dosimeters Based On Metal Oxide Filmsmentioning
confidence: 99%
“…In fact, the radiations with a high energy like gamma rays and X-rays can alter the concentration of oxygen vacancies and also create point defects and other structural defects in MOs [8]. Therefore, metal oxides can be used for the detection of high-energy radiation [9].…”
Section: Introductionmentioning
confidence: 99%